A new species of \(Billolivia\) (Gesneriaceae) from Vietnam - Long Vu, Ngoc; Cuong Nguyen, Hieu; Dang Tran, Huu; Luu, Hong Truong (Academia Journal of Biology, 2023)
Billolivia maiana is described as a new species narrowly endemic to Cu Prong mountain, Dak Lak province, Central Highlands of Vietnam. This third recorded yellow-flowered species of the genus is characterized by the absence of stolons, glabrous young leaves, smaller leaves with short petioles, compacted inflorescence with short peduncles, rays and pedicels, white upper lobes of corolla with yellow margin and purple lines throughout, undulate disc-lobes and glabrous ovary. The new taxon is described and illustrated with field photographs of detailed botanical characteristics and assessed as CR following the IUCN Redlist Categories. A key to all yellow-flowered Billolivia taxa is provided.